2016
DOI: 10.7567/jjap.55.08rb01
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and demonstration of 1 × 8 silicon–silica multi-chip switch based on optical phased array

Abstract: We experimentally demonstrated a 1 × 8 silicon–silica hybrid thermo-optic switch based on an optical phased array using a multi-chip integration technique. The switch consists of a silicon chip with optical phase shifters and two silica-based planar lightwave circuit (PLC) chips composed of optical couplers and fiber connections. We adopted a rib waveguide as the silicon waveguide to reduce the coupling loss and increase the alignment tolerance for coupling between silicon and silica waveguides. As a result, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Another feasible 1 × N optical switch is based on a phased array illustrated in Fig. 13(b) [99] . The optical wave is first divided into multiple beams by the first star coupler.…”
Section: Multi-path Switchable Delay Linesmentioning
confidence: 99%
“…Another feasible 1 × N optical switch is based on a phased array illustrated in Fig. 13(b) [99] . The optical wave is first divided into multiple beams by the first star coupler.…”
Section: Multi-path Switchable Delay Linesmentioning
confidence: 99%
“…A fast-optical switch employing digital micromirror device (DMD)based wavelength selective switch was demonstrated [7], and a review on optical switches for data centers was reported [8]. To realize a waveguide-based optical switch with high speed, siliconsilica hybrid structure [9] is promising since silicon provides excellent thermal properties, although it was reported the investigation to enhance the switching speed of the silica-based optical switch by optimizing the waveguide structure and using an over-driving technique [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, its application to data center network is considered, [9][10][11] where switching speed is an issue. To realize a high-speed optical switch, silicon-silica hybrid structure 12,13) is promising from the point of view of the thermal properties of silicon. [14][15][16][17][18][19][20][21][22][23] A conventional cascaded Mach-Zehnder (MZI) switch 24,25) is not suitable for hybrid structure since phase shifters are arranged in series.…”
Section: Introductionmentioning
confidence: 99%